Implementasi Design Thinking dalam Perancangan UI/UX Dashboard Monitoring Sales One Direction pada PT. XYZ - Siti Farah Fakhirah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Advancements in modern information technology continuously require companies to present complex data more effectively, especially within the scope of sales management and business decision-making. Dashboards are essential, interactive tools that enable professionals and managers to make strategic decisions quickly, confidently, and based on accurate data visualization. This study focuses on designing an intuitive and user-centered Sales Monitoring Dashboard UI/UX for One Direction at PT. XYZ by applying the five iterative stages of the Design Thinking method, namely empathize, define, ideate, prototype, and test. Key user needs identified include real-time performance summaries, streamlined navigation flow, informative visual hierarchy, and visuals that remain consistent with corporate identity and brand values. The System Usability Scale (SUS) test involving 19 respondents resulted in an excellent average score of 80.92. These findings demonstrate that the Design Thinking approach effectively produces a user-friendly, consistent, and data-driven dashboard interface that supports timely, accurate, and informed business decisions.